Rancang Model Sistem Mobile untuk Mesin Pengupas Kopi (Pulper) - Muh. Rinaldi; Iqbal Salim; Abdul Azis; Mursalim Mursalim (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
Pulping is one of the stages of coffee processing. There are various types of coffee pulpers owned by several farmers, but they are not mobile because they have a large construction, and there are several farmers who still use manual coffee peeling machines driven by human labor sources. The purpose of this research is to make a 3-dimensional design of a mobile type wet coffee pulper. The method is carried out starting from determining the capacity of the machine, analyzing the design, determining the dimensions, sketching each part of the machine, determining the material to form a complete design that is ready to be simulated. The results obtained in this study are a 3-dimensional design of a mobile pulper machine, which shows that the peeling machine is mounted on a modified motorcycle frame and uses the rotating power from the tip of the magnetic shaft of the motorcycle engine flywheel. The filling capacity of the hopper is 18 kg. The transmission system used is pulley and belt and transmits power from the engine to the pulper unit with an additional reduction shaft. The engine speed of 1200 rpm is reduced to 390 rpm so that the peeling cylinder has a speed of 110 rpm. The results of this research are expected to provide a reference for the physical fabrication of mobile pulper machine prototypes.